Cochlear implantation outcomes in cases of cochlear malformations...15th International Conference on Cochlear Implants and Other Implantable Auditory Technologies; 27th Jun 2018 - 30th Jun 2018; Antwerp, Belgium - Diab, Kh. M.; Daykhes, N. A.; Kondratchikov, D. S.; Pashchinina, O. A.; Yusifov, K. D.; Mikhalevich, A. E. (Journal of Hearing Science, 2018)
Objective: To demonstrate the benefits of implantation in patients with inner ear malformations. Patients and Methods: It has been performed 26 Cochlear Implantations (CI) on pediatric patients with Cochlear malformations to date. According to L. Sennaroglu, the malformations encountered included 3 common cavity (CC), 1 cochlear hypoplasia type II, type III and type IV, 2 common cavities, 3 incomplete partitions of of the cochlea type I (IP-I, cystic cochlea), 8 IP-II (Mondini deformity) and 7 IP-III. In cases of round window membrane presence, the CI was perform by classical method with transmembrane electrode insertion. In cases of common cavity and one IP I case, the round window membrane was not identifies and the electrode was insert via cochleostomy. CSF leak occurred in all cases of IP and common cavity. Results: The full insertion of electrodes of previously chosen length (from 11 to 27 mm) has been achieved in all 26 cases. In cases, whith gushers due to the absence of bone wall between the cochlea and IAC cerebrospinal fluid leakage were successfully stop by reliable packing cohleostomy/ round window niche using muscle flap and silicon stopper of electrode array. After 6 months sound processor activation, 5-7 years old children - understand words with an open choice of more than 90%. Children up to 5 years reached similar results closer to 12 months of using the systems. Speech of 5-7 years old children after 1 year using of the system was easy to understand by all. CI was less effective in cases with a CC. Children with malformed cochlea required an increasing of the adjustment session number. Conclusion: Good visualization of round window and transmembrane insertion of active electrode into spiral canal of cochlea in patients with inner ear malformations help to minimize the trauma of the spiral organ, control liquorrhea and improve postoperative auditory performance.